Studi Pemanfaatan Enceng Gondok (Eichhornia Crassipes) sebagai Bio-briket Ramah Lingkungan: Studi Eksperimental - Syamsul Bahri Widodo; Zainal Arif; Iskandar Yakob; Suheri Suheri; Dicky Maranata Sembiring (CV. IRA PUBLISHING, 2025)
Eichhornia crassipes (water hyacinth) is a fast-growing aquatic plant in tropical regions like Indonesia. Though often considered a weed, it remains underutilized as an alternative energy source. This study explores its potential as a solid fuel in the form of eco-friendly bio-briquettes. The production process includes drying, carbonization, sieving, mixing with binder, molding, and final drying. Laboratory tests involved proximate analysis and calorific value measurement. Results showed that the briquettes contained 9.61% moisture, 3.93% ash, 7.89% volatile matter, 78.57% fixed carbon, and a calorific value of 25.8 kJ/g. Compared to coconut shell briquettes, water hyacinth briquettes burn more slowly but offer cleaner and more stable combustion. These characteristics make them a suitable renewable energy source for households and small industries.